PERANCANGAN SISTEM PAKAR DIAGNOSA PENYAKIT TONSILITS MENGGUNAKAN METODE FORWARD CHAINING BERBASIS WEB - Vincent Vincent; Anggia Dasa Putri (Computer Based Information System Journal, 2025)
A common ear, nose, and throat (ENT) condition that typically affects people of all ages is tonsillitis. Tonsillitis related issues can be avoided with a diagnosis procedure. In the medical field, expert systems a technology that can solve issues using expert knowledge are frequently employed to diagnose illnesses. People can determine whether they have tonsillitis or not by simply use the system for early diagnosis. The Forward Chaining technique is applied on the expert system. Because the Forward Chaining approach can trace the rules from user inputs and then derive conclusions, it is usually used. The Rapid Application Development (RAD) approach is implemented during application design and development simply because the method has the benefit of enabling the quick development of applications. The tonsillitis expert system was developed using the PHP programming language and MySQL database, which facilitate the maintenance of facts and knowledge. From the research results, it is shown that the system were able to help diagnose tonsillitis quickly and provide recommendations for treatments. Expert system to diagnose tonsillitis is expected to raise public awareness of the illness's dangers and the need of staying well. The system should also be able to help the general public make well informed judgments regarding treatment of tonsillitis.